1976
DOI: 10.1161/01.cir.53.2.286
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive evaluation of ventricular hypertrophy in professional athletes.

Abstract: Athletes often exhibit ECG findings which are considered to be abnormal. Therefore, we used noninvasive graphic methods to study 42 active professional male basketball players, ranging in age from 21 to 31 years, without clinically evident heart disease. Of the 42, 11 (25%) met the Romhilt-Estes ECG voltage criteria for left ventricular hypertrophy, and 12 (29%) satisfied VCG criteria for left ventricular enlargement; nine (21%) had left ventricular hypertrophy by both methods. In 33 subjects (79%) the 0.04 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
2
3

Year Published

1976
1976
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(54 citation statements)
references
References 49 publications
6
43
2
3
Order By: Relevance
“…4 Subsequent work with 2-dimensional echocardiography confirmed underlying LV hypertrophy and dilation. 5 To help understand the physiological mechanisms involved in various exercises, they can be broadly classified as either "isotonic" or "isometric" based on the hemodynamic mechanisms that occur during these activities. Isotonic (endurance) exercise involves sustained elevations in cardiac output with normal or reduced peripheral vascular resistance.…”
Section: Left Ventricular Adaptations In Athletic Heart Syndromementioning
confidence: 99%
“…4 Subsequent work with 2-dimensional echocardiography confirmed underlying LV hypertrophy and dilation. 5 To help understand the physiological mechanisms involved in various exercises, they can be broadly classified as either "isotonic" or "isometric" based on the hemodynamic mechanisms that occur during these activities. Isotonic (endurance) exercise involves sustained elevations in cardiac output with normal or reduced peripheral vascular resistance.…”
Section: Left Ventricular Adaptations In Athletic Heart Syndromementioning
confidence: 99%
“…9,25 Subsequent work with 2-dimensional echocardiography confirmed underlying LV hypertrophy and dilation. 26 Italian physicianscientists have contributed a great deal to our understanding of LV structure in athletes using data derived from their long-standing preparticipation screening program. Pelliccia et al 27 reported echocardiographic LV end-diastolic cavity dimensions in a large group (nϭ1309) of Italian elite athletes.…”
Section: The Left Ventriclementioning
confidence: 99%
“…Several studies of left and right ventricular volumes in athletes have shown physiological adaptation to training that differs from the pathological remodeling found in diseases such as hypertrophic and dilated cardiomyopathies (1)(2)(3)(4)(5). Furthermore, total heart volume (THV) has been shown to increase with long term endurance training, and there is a strong correlation between THV and peak oxygen uptake (VO 2 peak) (4).…”
Section: Introductionmentioning
confidence: 99%